World Trade Center (WTC) attack: its impact to the Kuala Lumpur Stock Exchange (KLSE) and Malaysia Foreign Exchange (FOREX) market / Muhamad Nazri Abdul Rahman - Abdul Rahman, Muhamad Nazri (2002)
This project paper is prepared to futfill the requirement as needed by the Facuty of Business and Management, MARA University of Technology. For this purpose, I have selected a topic entitled, "World Trade Center (WTC) Attack: Its Impact to the Kuala Lumpur Stock Exchange (KLSE) and Malaysia Foreign Exchange (FOREX) Market". United State of America is one of the economic leaders in the world. Most of the country in the word are depending their economy on United States economy. Malaysia is one of the countries that are not excepted from depending their economy to United States. This is because America is one of the biggest importers of Malaysian made product. If America faced an economic problem, so Malaysia cannot export their product and cause the deficit in Balance of Payment. On September 11 2001, the world was shocked by the destruction of World Trade Center (WTC) in New York. The WTC building was attacked by two aeroplanes and caused a lot of person died due to that attack. The President of United State of America, George W. Bush believed that, the attack was done by the Islamic terrorists from Afghanistan. After the WTC was attacked, it caused the American economic turn down. This is because they have their focus on their military to attack Afghanistan and ignore their economic development effort. Due to this, it has cause most of the country in the world including Malaysia to face economic problem.